Global financial investigations : forensic accounting in practice - Gore, Amanda (Forensic accountant) (Routledge, 2025)
"Adopting a case-based approach, Global Financial Investigations introduces readers to the fascinating world of forensic accounting and investigating transnational financial crimes, providing an overview of core concepts and current industry trends, together with practical guidance to equip students with the knowledge required to combat complex financial crimes. By exploring the different types of financial investigations led by various law enforcement agencies, this accessible text covers a breadth of forensic accounting and broader financial crime issues, from investigating illicit trade and reconstructing financial records, to conducting regulatory investigations. Supported by real-world cases from different geographic regions, students will learn the practical hands-on forensic accounting and financial investigation skills required in today's work environment. Learning features include: -a wealth of practical examples highlighting explanations of the main terminology and concepts - engaging real-world case studies from multiple regions, including Europe, Africa, Latin America, North America, New Zealand and Asia - start-of-chapter learning objectives and a summary of key learning points to reinforce learning - end-of-chapter discussion questions, multiple choice questions and recommendations for further reading. Written by a highly experienced professional and educator in forensic accounting, Global Financial Investigations is the ideal textbook for undergraduate and graduate-level students of courses in forensic accounting, financial crime investigation and fraud investigation"-- Provided by publisher.
Keywords: Forensic accounting.; Commercial crimes -- Investigation.; Transnational crime.; elektronické knihy; electronic books